Aqui e lá: olhares e fronteiras entre a comunidade indígena Pataxó e a sociedade envolvente no município de Carmésia/MG - José Dias Neto (2019)
The ways that men establish, perceive, appropriate, attach meaning and bind (affectively or otherwise) to places have been the object of reflection of the humanistic and cultural geographies and have occupied prominent role within human geography today. This can be justified by the symbolic character inherent in this dynamic of collective appropriation which is integrated into the culture and has the capacity to guide ways of life, identities, traditions, values and other sociocultural structures that are components of this process. For that matter, the relationship between the Subject and the Place, established and culturally apprehended, is a useful construct for the understanding of social forms, allowing the assessment of the sociability that integrates the territories, bringing the reflections of Geography, Sociology and Anthropology closer together. The anthropologist Darcy Ribeiro, when evaluating the Brazilian social configuration, observes that indigenous communities in contact with the hegemonic surrounding society, instead of being assimilated, were subjected to a series of situations of violence, including cultural and territorial loss and, in the end, but not infrequently, of their lives. With the emergence of the contemporary multiculturalist paradigm, the relationship between indigenous communities and the surrounding society is subject to revaluation, since current times are seen as a moment of major role for indigenous people in the political and media arena, where they can be seen with sympathy by society at large. However, within the context of everyday relations, is this paradigm shift reflected also in better conditions of interaction between indigenous communities and hegemonic society that share the same place? In this perspective, this research proposes to reflect on the perception of the population of Carmésia / MG in relation to the Indigenous Land Fazenda Guarani, occupied by the indigenous community Patasho. Thus, from an ethno-geographic approach that seeks to foster a dialogue between ethnographic and phenomenological methods, field data will be collected through semi-structured scripts and informal conversations with residents, in order to try to identify the way in which the surrounding society perceives and is linked to the indigenous community. It will also raise the perception, in particular, of the city's children's public through the application of mental maps in schools of the fundamental level, so as to consider the formation of the thought of a next generation about the indigenous community, the processes and the very way this perception has been culturally constructed through socialization. With this work, we seek to contribute to the reflections about the perception, relationship and possibilities of socio-territorial interaction between indigenous communities and their environment.